Nilai Religi Dalam Tradisi Aruh Maulud Suku Banjar Di Desa Lubuk Bayas - Aisyah, Siti Nur; Nasution, Hasnah (Ulumuddin: Jurnal Ilmu-ilmu Keislaman, 2025)
This ethnographic study aims to explore the religious values embedded in the Aruh Maulud tradition practiced by the Banjar community in Lubuk Bayas Village. Data were collected through participatory observation, in-depth interviews with traditional leaders and community members, and documentation during the event. The findings reveal that the Aruh Maulud tradition is not only a commemoration of the birth of the Prophet Muhammad (PBUH), but also embodies religious values such as Islamic brotherhood (ukhuwah Islamiyah), generosity and charity, as well as gratitude to Allah SWT. These values are manifested in religious activities such as maulid recitations, the sharing of traditional food, and harmonious social interactions among community members. In conclusion, the Aruh Maulud tradition in Lubuk Bayas Village plays a significant role in strengthening the religious and cultural identity of the Banjar people, and serving as a medium for imparting Islamic values to the younger generation.